The Strengthening of Regional Competitiveness Through the Partnership Model of Fresh Water Fish farming in Muaro Jambi Regency - Susi Desmaryani (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2017)
The pattern of the partnership is one solution to help the problems faced by farmers catfish, catfish farmers in the district of Kumpeh Uluh Muaro Jambi of regency has a broad enough market share, not only in the province of Jambi alone but has been extended to the provinces of Riau and South Sumatra. While catfish farmers have a market contraints. Subcontracting partnership pattern and the pattern of general trade partnerships, could not break the problem of catfish farmers, especially in meeting the needs of the market. The purpose of the study was to determine the existing condition of catfish farmers in the district of Ulu Kumpeh Muaro Jambi of Regency, and how to model a partnership as a reinforcement of the competitiveness of catfish farmers in the district of Ulu Kumpeh Muaro Jambi of Regency. The method used was a case study with descriptive research type. A sample of 50 respondents. How sampling was done purposive sampling. Technical analysis of data using descriptive analysis. The results show that the pattern of subcontracting partnership and general partnership pattern of trade has not been implemented in accordance UU No 20 in 2008 when a partnership is not profitable catfish farmers and government intervention is not maximized as a coordinator, facilitator and supervisor (UU No 20 Tahun 2008 tentang Usaaha Mikro, Kecil dan Menengah, 2008). Pattern of Partnership Plasma core is a partnership model that can improve the performance of farmers catfish, involving BUMDes (the core) to implement downstream fishery policy (marketing), and provider of capital, together with state-owned enterprises, and universities to transfer knowledge is and transfer of technology, so that catfish of farmer (as plasma) competitiveness. The study results recommend to make a model of partnership pattern plasma core, Partner is BUMDes and catfish farmers (as plasma). The government increased its function as a facilitator, coordinator, and supervisor in partnership pattern plasma core.